Human resource management-III : BBA 6th semester and for other professional courses - Sahni, N.K (Kalyani Publishers, 2011)
Human resource management-III : BBA 6th semester and for other professional courses / Sahni, N.K. -- Kolkata: Kalyani Publishers, 2011 658.3 Sa231e2 2nd rev, ed. No. of Copies : 1